Confirming a Historical Diagnosis of Multiple Sclerosis: Challenges and Recommendations. Issue 3 (June 2022) - Solomon, Andrew J.; Arrambide, Georgina; Brownlee, Wallace; Cross, Anne H.; Gaitan, María I.; Lublin, Fred D.; Makhani, Naila; Mowry, Ellen M.; Reich, Daniel S.; Rovira, Àlex; Weinshenker, Brian G.; Cohen, Jeffrey A.
Abstract : Patients with a historical diagnosis of multiple sclerosis (MS)—a patient presenting with a diagnosis of MS made previously and by a different clinician—present specific diagnostic and therapeutic challenges in clinical practice. Application of the McDonald criteria is most straightforward when applied contemporaneously with a syndrome typical of an MS attack or relapse; however, retrospective application of the criteria in some patients with a historical diagnosis of MS can be problematic. Limited patient recollection of symptoms and evolution of neurologic examination and MRI findings complicate confirmation of an earlier MS diagnosis and assessment of subsequent disease activity or clinical progression. Adequate records for review of prior clinical examinations, laboratory results, and/or MRI scans obtained at the time of diagnosis or during ensuing care may be inadequate or unavailable. This article provides recommendations for a clinical approach to the evaluation of patients with a historical diagnosis of MS to aid diagnostic confirmation, avoid misdiagnosis, and inform therapeutic decision making.